Pendaftaran Kewarganegaraan Anak Hasil Perkawinan Campuran - Novitasari Kusuma Dewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
Marriages that occur between foreign nationals and Indonesian citizens are mixed marriages. The development of the times makes it easier for someone to interact, so that mixed marriages occur which involve differences in nationality between partners. Based on this, this study aims to analyze and describe the regulation of the citizenship status of children from mixed marriages and registration of citizenship of children from mixed marriages. The method used in this study is normative law that uses a statutory approach and analysis of legal concepts derived from the literature. The results of this study indicate that the regulation of the citizenship status of children resulting from mixed marriages is regulated in Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia. Children resulting from mixed marriages have the right to declare and choose their citizenship no later than 3 (three) years after turning 18 (eighteen) years old or already married. The procedure for registering children resulting from mixed marriages must be registered in writing in the Indonesian language by a legal guardian or parent. Registration is done online through the pewarganegaraan.ahu.go.id website or by submitting complete requirements to the President of the Republic of Indonesia inside or outside the territory of Indonesia, the Minister of Law and Human Rights.